Elaboração e implantação de um modelo de capacitação para profissionais de CAPSI na assistência a crianças com transtornos do espectro autista - Silva, Luciana Coltri e (2016)
In Brazil we have a Unified National Health System (SUS), that has the doctrinal principles the Universality, the Integrality, the Equity, the Decentralization and the Citizen Participation. About mental health, were created the Psychosocial Community Care Centers (CAPS) and Psychosocial Community Care Center for Children and Adolescents (CAPSI), for the for child and adolescents care, until 24 years old, The children with Autism Spectrum Disorders (ASD) are one of the clinical groups that most use the service of the CAPSI in São Paulo, then it is expected that mental health professionals of SUS are prepared to answer this demand. Thus, the main goal of this study objectives were the development, implementation and evaluation of a training program directed to professionals working with these children in CAPSI the North Zone of São Paulo. The study participants were 14 health professionals from CAPSI located in the north of São Paulo, who have gone through a training with 6 phases: (1) pre-intervention observation; (2) preparation material (3) meetings with professionals to survey the demand; (4) workshops; (5) final meeting to discuss cases and (6) online supervision. In these stages were used 3 instruments: (1) Questionnaire KAP - knowledge, attitudes and practices; (2) vídeos with questions about the expertise on issues with children with ASD and (3) satisfaction questionnaire. The training proved feasible following the mold of Permanent Education and Taking into account specifics of how this type of work institution is. The results of this study showed improvement in the average level of knowledge of the professionals from CAPSI, with hits overall computation of the videos after the training compared to pre -intervention phase (avarage increase: 3,7 [DP + 2,3], p <0,01). It was also identified improved performance of the study participants according to the KAP questionnaire with increase in total score after intervention (p = 0,020) and in the subscales knowledge (p=0,003) and atitudes (p =0,050). The main conclusions of the study are that: (1) the proposed training model for CAPSI professionals for to the assistance of children with ASD is feasible, following the mold of Permanent Education; (2) there was an improvement in the degree of knowledge of professionals, evidenced by evaluation videos except for some themes) and assessment by questionnaire KAP; (3) an improvement in the attitudes of trained professionals and (4) participants assessed the qualification positively.